LêbrailleTWT - providing visual accessibility to twitter on touchscreen devices - Façanha, Agebson R.; Araújo, Maria da C. C.; Viana, Windson; Pequeno, Mauro C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The increasing use of social networks via touch screen interfaces on smartphones and tablets has brought enormous benefits to the mobile applications usability. However, access to information via these devices represents a new challenge of interaction for users with visual impairments. In this context, this paper describes a study on the issue of visual accessibility in virtual social networks, specifically on Twitter. Moreover, we have developed a mobile application to access Twitter via touch screen smartphones using the Android platform. This application provides access to blind people with audio feedback and a writing tool based on Braille. The mobile application presents itself as a solution to facilitate the interaction of the visually impaired users in this social network. In this paper, we also describe a study of use of the application with a group of blind people.